2018
DOI: 10.1155/2018/6015753
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity and Excitation-Inhibition Balance in the Dentate Gyrus: Insights fromIn VivoRecordings in Neuroligin-1, Neuroligin-2, and Collybistin Knockouts

Abstract: The hippocampal dentate gyrus plays a role in spatial learning and memory and is thought to encode differences between similar environments. The integrity of excitatory and inhibitory transmission and a fine balance between them is essential for efficient processing of information. Therefore, identification and functional characterization of crucial molecular players at excitatory and inhibitory inputs is critical for understanding the dentate gyrus function. In this minireview, we discuss recent studies unrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…CB‐deficient mice revealed that CB is necessary for the synaptic localization of GABA A Rs and gephyrin in various brain areas particularly hippocampus, amygdala and cerebellum (Papadopoulos et al., 2007, 2008). CB‐deficient mice also have impaired synaptic function in the hippocampus and dentate gyrus and impaired synaptic plasticity (Jedlicka et al., 2009, 2018; Papadopoulos et al., 2007). These results make our hippocampal neuronal cultures highly suitable to address the synaptic role of the CBSH3+ and CBSH3− isoforms by specifically knocking them down with shRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CB‐deficient mice revealed that CB is necessary for the synaptic localization of GABA A Rs and gephyrin in various brain areas particularly hippocampus, amygdala and cerebellum (Papadopoulos et al., 2007, 2008). CB‐deficient mice also have impaired synaptic function in the hippocampus and dentate gyrus and impaired synaptic plasticity (Jedlicka et al., 2009, 2018; Papadopoulos et al., 2007). These results make our hippocampal neuronal cultures highly suitable to address the synaptic role of the CBSH3+ and CBSH3− isoforms by specifically knocking them down with shRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Collybistin-deficient mutants show that CB is essential for postsynaptic clustering of GABA A Rs and gephyrin in several brain regions including hippocampus, amygdala and cerebellum, but not in the cerebral cortex and other brain areas (Papadopoulos et al, 2007(Papadopoulos et al, , 2008. CB-deficient mice also have impaired synaptic function in the hippocampus and dentate gyrus (Jedlicka et al, 2009(Jedlicka et al, , 2018Papadopoulos et al, 2007). In spite of these synaptic phenotypes being manifested only in specific brain regions of the CB-deficient mutants, CB mRNA and protein is expressed by neurons through all brain regions, including the cerebral cortex (Kins et al, 2000;Patrizi et al, 2012), http://mouse.brain -map.org/exper iment/ show/70231011.…”
Section: Introductionmentioning
confidence: 99%
“…Recordings in intact mice allow the assessment of distinct properties of neuronal network behaviour that are often difficult to replicate in acute slices or cultures, such as the influence of inhibition on firing activity 29 . Earlier studies have reported that inhibitory synapse function was severely compromised in both acute slices and primary neuronal cultures of null-mutant Nbea neurons 4 , 5 , 7 , 8 .…”
Section: Resultsmentioning
confidence: 99%
“…CB KO mice exhibited elevated anxiety levels and impaired spatial memory (Table 2; Supplementary Table S1), and showed reduced GABAergic transmission, increased LTP, and decreased long-term depression (LTD) in hippocampal CA1 region [63]. Two studies using this mouse line investigated electrophysiological characteristics in hippocampal dentate gyrus (DG) region, demonstrating that CB plays an important role in maintaining normal granule cell excitability, GABAergic network inhibition, and synaptic plasticity [64,65].…”
Section: Arhgef9 (Sfari Gene Score: 1 High Confidence)mentioning
confidence: 99%